SISTEM REDUPLIKASI BAHASA BUGIS (SUATU KAJIAN TRANSFORMASI GENERATIF) - Restu Nurul Alfadilah, (JOEL: Journal of Educational and Language Research, 2022)
Regional languages in Indonesia have an influence on the formation and development of the Indonesian language. The Bugis language is one of the regional languages present in the province of South Sulawesi. Not always someone who speaks this language can analyze a precise language, both the mother tongue which is studied or will be studied. The problem raised in this study is how to shape the Bugis language reduplication system (a generative transformation study). The objective of the research is to describe the form of the Bugis language reduplication system (study of generative transformation). The method used in this research is qualitative descriptive. The data in this study are oral data. The techniques used to collect the data in this study were recording techniques, note taking techniques and snowball sampling techniques. Based on the results of the Bugis language reduplication system research (a study of generative transformation), not all reduplications in the Bugis language are transformed. Intact reduplication does not show symptoms of transformation because the external and internal structures remain the same. Only partial reduplication and apposed reduplication underwent transformation and not all of them underwent transformation. The transformations that occur in the Bugis language are transformation by omission, transformation by permutation, transformation by addition, and transformation by change.